2002
DOI: 10.1091/mbc.01-02-0302
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Down-regulation of ROCKI/Rho-kinase through an MEK-dependent Pathway Leads to Cytoskeleton Disruption in Ras-transformed Fibroblasts

Abstract: Transformation by oncogenic Ras profoundly alters actin cytoskeleton organization. We investigated Ras-dependent signaling pathways involved in cytoskeleton disruption by transfecting normal rat kidney (NRK) cells with different Ras mutants. RasV12S35, a mutant known to activate specifically the Raf/MAPK pathway, led to stress fiber and focal contact disruption, whereas the adherens junctions remained intact. Next, we found that pharmacological inhibition of MEK was sufficient to restore the cytoskeletal defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 57 publications
7
51
1
Order By: Relevance
“…Association of the Rho and ERK pathways for regulation of actin filaments has also been shown in a variety of cells, including vascular cells [19][20][21][22][23]. In the present study, expression of phosphorylated ERK (p44/p42) was increased from 2.5 min to 15 min after stimulation with 5-HT in a time-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 79%
“…Association of the Rho and ERK pathways for regulation of actin filaments has also been shown in a variety of cells, including vascular cells [19][20][21][22][23]. In the present study, expression of phosphorylated ERK (p44/p42) was increased from 2.5 min to 15 min after stimulation with 5-HT in a time-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 79%
“…The p38 MAPK pathway may enhance cell motility by regulating actin remodeling factor HSP27 (Hedges et al, 1999) and by affecting actin polymerization and cell contractility (Huot et al, 1998;Hedges et al, 1999;Bakin et al, 2002). MEK-ERK may regulate cell motility by preventing formation of extensive actin stress fibers via suppression of tropomyosin induction by TGF-b1 (Bakin et al, 2004) or inhibition of RhoA-Rho kinase pathway (Sahai et al, 2001;Pawlak and Helfman, 2002). JNK may regulate motility by modulating the dynamics of microtubules (Huang et al, 2004) or by affecting the assembly/ stability of focal adhesion complexes via phosphorylation of paxillin and Spir, a WASP family protein (reviewed by Huang et al (2004)).…”
Section: Discussionmentioning
confidence: 99%
“…In HT1080 human fibrosarcoma cells containing oncogenic N-Ras, both Rac and RhoA activity were increased compared with cells lacking the mutant N-Ras; Rac and RhoA activities were also increased when cells lacking the mutant N-Ras were stably transfected with constitutively active Raf or MEK (18). In K-Ras(V12)-transformed normal rat kidney cells, no significant change of RhoA activity was observed compared with untransformed cells (23). Several older studies reported loss of stress fibers in Ras-transformed Rat1 cells, with restoration of stress fibers upon transfection of constitutively active RhoA, suggesting loss of RhoA activity in the Ras-transformed cells (7,24); others reported increased stress fibers in Rastransformed breast cancer cells and NIH 3T3 cells without direct measurement of Rho activity (14,15).…”
mentioning
confidence: 95%